Applying Best Practice Online Learning, Teaching, and Support to Intensive Online Environments: An Integrative Review - Roddy, Chantal; Amiet, Danielle Lalaine; Chung, Jennifer; Holt, Christopher; Shaw, Lauren; McKenzie, Stephen; Garivaldis, Filia; Lodge, Jason M.; Mundy, Matthew Edward (Frontiers in Education, 2017)
Demand for flexible online offerings has continued to increase as prospective students seek to upskill, re-train, and undertake further study. Education institutions are moving to intensive modes of online study delivered in six- to eight-week study periods which offer more frequent intake periods. Prior literature has established key success factors for non-intensive (12-13 week) online offerings; for teachers, skill development is critical to promote a flexible, responsive approach and maintain technological capabilities; for students, an ability to navigate the technology, interact with the learning environment in meaningful ways, and self-regulate learning is important, as the absence of physical infrastructure and opportunities for face-to-face interactions in online environments places a greater emphasis on alternate forms of communication and support. The current paper explores known best practice principles for online instructors, students and student support, and considers how these might apply to intensive online environments. It is suggested that the accelerated nature of learning in intensive settings may place additional demands on students, instructors and support mechanisms. Further research is imperative to determine predictors of success in online intensive learning environments.